Immune–Inflammatory Biomarkers Predict Cognition and Social Functioning in Patients With Type 2 Diabetes Mellitus, Major Depressive Disorder, Bipolar Disorder, and Schizophrenia: A 1-Year Follow-Up Study - Garés-Caballer, Marta; Sánchez-Ortí, Joan Vicent; Correa-Ghisays, Patricia; Balanzá-Martínez, Vicent; Selva-Vera, Gabriel; Vila-Francés, Joan; Magdalena-Benedito, Rafael; San-Martin, Constanza; Victor, Victor M.; Escribano-Lopez, Irene; Hernandez-Mijares, Antonio; Vivas-Lalinde, Juliana; et al. (Frontiers in Neurology, 2022)
Background: Systemic, low-grade immune-inflammatory activity, together with social and neurocognitive performance deficits are a transdiagnostic trait of people suffering from type 2 diabetes mellitus (T2DM) and severe mental illnesses (SMIs) such as schizophrenia (SZ), major depressive disorder (MDD), and bipolar disorder (BD). We aimed to determine if immune-inflammatory mediators were significantly altered in people with SMIs or T2DM compared with healthy controls (HC) and whether these biomarkers could help predict their cognition and social functioning 1 year after assessment. Methods: We performed a prospective, 1-year follow-up cohort study with 165 participants at baseline (TB), including 30 with SZ, 42 with BD, 35 with MDD, 30 with T2DM, and 28 HC; and 125 at 1-year follow-up (TY), and determined executive domain (ED), global social functioning score (GSFS), and peripheral blood immune-inflammatory and oxidative stress biomarkers. Results: Participants with SMIs and T2DM showed increased peripheral levels of inflammatory markers, such as IL-10 (p< 0.01; η²p=0.07) and TNF-α (p< 0.05; η²p=0.08), and oxidative stress biomarkers like ROS (p< 0.05; η²p=0.07) and mROS (p< 0.01; η²p = 0.08). Different combinations of the exposed biomarkers anticipated 46-57.3% of the total ED and 23.8-35.7% of GSFS for the participants with SMIs. Limitations: Participants’ treatment, as usual, was continued without no specific interventions, thus it was difficult to anticipate substantial changes related to the psychopharmacological pattern. Conclusion: People with SMIs show significantly increased levels of peripheral immune-inflammatory biomarkers, which may contribute to the neurocognitive and social deficits observed in SMIs, T2DM, and other diseases with systemic immune-inflammatory activation of chronic development. These parameters could help identify the subset of patients who could benefit from immune-inflammatory modulator strategies to ameliorate their functional outcomes.